Possibilities and challenges for No-till practices in Bulgaria - Basch, G. (2017)
What is No-till? From No-till to Conservation Agriculture (CA) Why use No-till/CA? Where is No-till/CA practiced? The Bulgarian context The Ups The challenges No-till/CA in the context of CAP